Trends and characteristics of US emergency department visits, 1997-2007 - Tang, Ning; Stein, John; Hsia, Renee Y; Maselli, Judith H; Gonzales, Ralph (JAMA : the journal of the American Medical Association, 2010)
The potential effects of increasing numbers of uninsured and underinsured persons on US emergency departments (EDs) is a concern for the health care safety net. To describe the changes in ED visits that occurred from 1997 through 2007 in the adult and pediatric US populations by sociodemographic group, designation of safety-net ED, and trends in ambulatory care-sensitive conditions. Publicly available ED visit data from the National Hospital Ambulatory Medical Care Survey (NHAMCS) from 1997 through 2007 were stratified by age, sex, race, ethnicity, insurance status, safety-net hospital classification, triage category, and disposition. Codes from the International Classification of Diseases, Ninth Revision (ICD-9), were used to extract visits related to ambulatory care-sensitive conditions. Visit rates were calculated using annual US Census estimates. Total annual visits to US EDs and ED visit rates for population subgroups. Between 1997 and 2007, ED visit rates increased from 352.8 to 390.5 per 1000 persons (rate difference, 37.7; 95% confidence interval [CI], -51.1 to 126.5; P = .001 for trend); the increase in total annual ED visits was almost double of what would be expected from population growth. Adults with Medicaid accounted for most of the increase in ED visits; the visit rate increased from 693.9 to 947.2 visits per 1000 enrollees between 1999 and 2007 (rate difference, 253.3; 95% CI, 41.1 to 465.5; P = .001 for trend). Although ED visit rates for adults with ambulatory care-sensitive conditions remained stable, ED visit rates among adults with Medicaid increased from 66.4 in 1999 to 83.9 in 2007 (rate difference, 17.5; 95% CI, -5.8 to 40.8; P = .007 for trend). The number of facilities qualifying as safety-net EDs increased from 1770 in 2000 to 2489 in 2007. These findings indicate that ED visit rates have increased from 1997 to 2007 and that EDs are increasingly serving as the safety net for medically underserved patients, particularly adults with Medicaid.